Functional Characterization of Ecdysis Triggering Hormone Receptors (AgETHR-A and AgETHR-B) in the African Malaria Mosquito, Anopheles gambiae - Jindal, Vikas; Park, Yoonseong; Kim, Donghun (Frontiers in Physiology, 2021)
Insect ecdysis behavior, shedding off the old cuticle, is under the control of specific neuropeptides with the top command by the ecdysis triggering hormone (ETH). We characterized the ETH receptor (ETHR) of the malaria mosquito, Anopheles gambiae, by manual annotation of the NCBI gene (AGAP002881) and functional analysis, using the heterologous expression system in a mammalian cell line. The two splicing variants of ETHRs, AgETHR-A and AgETHR-B, a conserved feature among insects, consisted of four (552 aa) and five exons (635 aa), respectively. The main feature of manual annotation of the receptor was a correction of N-terminal and exon-intron boundaries of an annotated gene (AGAP002881). Interestingly, the functional expression of the receptor in Chinese hamster ovarian (CHO) cells required modification of the transcription initiation site for mammalian Kozak consensus. In the calcium mobilization assay using the heterologous expression of each receptor, AgETHR-B showed a higher sensitivity to AgETH-1 (28 times) and AgETH-2 (320 times) than AgETHR-A. The AgETHRs showed specificity only to the ETH group of peptides but not to other groups carrying the C-termini motifs as PRXamide, such as pyrokinin1/DH and pyrokinin2/PBAN. AgETHR-B responded to different ETH variants of other insect species more promiscuously than AgETHR-A. The system we have established for the AgETHRs in this study will allow us to expand the scope into developing the AgETHRs as a new pesticidal target.